Hemiparetic cerebral palsy: etiological risk factors and neuroimaging Paralisia cerebral hemiparética: fatores de risco etiológico e neuroimagem - Ana Maria Sedrez Gonzaga Piovesana; Maria Valeriana Leme de Moura-Ribeiro; Verônica de Araújo Zanardi; Vanda Maria Gimenes Gonçalves (Arquivos de Neuro-Psiquiatria)
The purpose of this paper, which was conducted on 175 children with hemiparetic cerebral palsy (H-CP), was to verify the etiological risk period for this disease. Etiological risk factors (ERF) were detected through anamnesis: 23% in the prenatal period, 18% in the perinatal period and 59% of the patients the period was undefined (ERF in the prenatal and perinatal period was 41% and no ERF was 18% of the cases. The computerized tomographic scan (CT) and MRI were performed on all the patients, who were then classified according to their etiopathogenic data: CT1= normal (18%); CT 2= unilateral ventricular enlargement (25%); CT 3= cortical/ subcortical cavities (28%); CT4= hemispheric atrophy and other findings (14%); CT 5= malformations (15%). CT 5 was associated with physical malformations beyond the central nervous system and with prenatal ERF's , while CT 2 was associated with the perinatal ERF's, mainly in premature births. Magnetic resonance imaging was performed on 57 patients and demonstrated a good degree of concordance with the CT. Etiology remained undefined in only 37% of the cases after neuroimaging was related to ERF. A high perinatal RF frequency (59%) was observed and emphasized the need for special care during this period. Foram estudadas 175 crianças com paralisia cerebral hemiparética (PC-H) para elucidar o período de risco etiológico. Através da anamnese constataram-se fatores de risco para etiologia (FRE) pré-natal em 23%, perinatal em18% e período indefinido em 59% dos pacientes (com FRE pré e perinatal 41% e sem FRE 18%). A tomografia computadorizada (TC) foi realizada em todos os sujeitos e classificada de acordo com dados etiopatogênicos em: TC1= normal (18%); TC2= alargamento ventricular unilateral (25%); TC3= cavidades córtico-subcorticais (28%); TC4= atrofia hemisférica e outros achados (14%); TC5= malformações (15%). A TC5 se associada a malformações físicas fora do sistema nervoso central e aos FRE pré-natais e a TC2 aos perinatais, principalmente, nascer prematuro. A ressonância magnética foi realizada em 57 sujeitos demonstrando boa concordância com a TC. Após associação da neuroimagem e FRE a etiologia ficou indefinida em apenas 37%. Constatou-se alta frequência de FRE perinatais (59%), alertando para melhores cuidados neste período.